An Evaluation of the National Learning Network Materials Programme - Armstrong-Buisseret, Laurel E. (2010)
The National Learning Network (nln) materials are digital learning objects developed for English FE colleges as part of a pioneering Government initiative to increase the use of Information Communications Technology (ICT) in the post-16 sector. This study explores the nln materials programme and the differences it made. Practitioners, NLN development partners and key stakeholders were surveyed and interviewed to identify barriers and enablers uptake of the nln materials, and to assess their current use.